2019
DOI: 10.1016/j.celrep.2019.05.107
|View full text |Cite
|
Sign up to set email alerts
|

CPF Recruitment to Non-canonical Transcription Termination Sites Triggers Heterochromatin Assembly and Gene Silencing

Abstract: Highlights d CPF is required for RNAi-independent assembly of heterochromatin domains d YTH family protein Mmi1 loads CPF at non-canonical termination sites in gene bodies d Mmi1 and CPF promote Dhp1 XRN2 and RNAPII pileup to trigger heterochromatin assembly d CPF is globally required for silencing of genes regulated by Clr4 SUV39H

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(67 citation statements)
references
References 86 publications
6
57
0
Order By: Relevance
“…S5). This process parallels with the cleavage and polyadenylation factor (CPF)-mediated facultative heterochromatin assembly in yeast (33), the exact mechanism of which is still unknown.…”
Section: Discussionmentioning
confidence: 97%
“…S5). This process parallels with the cleavage and polyadenylation factor (CPF)-mediated facultative heterochromatin assembly in yeast (33), the exact mechanism of which is still unknown.…”
Section: Discussionmentioning
confidence: 97%
“…TRAMP containing Cid14, a member of the Trf4 family of poly(A) polymerases, targets RNAs into degradation machineries that include the exosome. Both RNAi-dependent and RNAi-independent mechanisms work in parallel to target CLRC to the repetitive DNA sequences located in the constitutive heterochromatin domains [71][72][73][74][75][76][77].…”
Section: Rnai-mediated Silencing Machinerymentioning
confidence: 99%
“…Related to Seb1, a recent study identified components of the cleavage and polyadenylation factor (CPF) complex as positive regulators of RNAi-independent heterochromatin silencing (Vo et al, 2019). A YTH family RNA-binding protein Mmi1 recruits CPF to the noncanonical termination sites, promoting termination of these noncoding genes and facilitating heterochromatin assembly (Vo et al, 2019).…”
Section: Parallel Examples Of Cotranscriptional Processing Linked Witmentioning
confidence: 99%
“…Related to Seb1, a recent study identified components of the cleavage and polyadenylation factor (CPF) complex as positive regulators of RNAi-independent heterochromatin silencing (Vo et al, 2019). A YTH family RNA-binding protein Mmi1 recruits CPF to the noncanonical termination sites, promoting termination of these noncoding genes and facilitating heterochromatin assembly (Vo et al, 2019). Notably, interaction between CPF and Seb1 was observed (Lemay et al, 2016;Wittmann et al, 2017;Larochelle et al, 2018), providing additional evidence that termination-related factors play important roles in gene silencing.…”
Section: Parallel Examples Of Cotranscriptional Processing Linked Witmentioning
confidence: 99%